2019
DOI: 10.1002/aoc.4729
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of multi‐walled carbon nanotubes by the baclofen drug to immobilize palladium nanoparticles and catalyze Sonogashira coupling reactions

Abstract: The baclofen‐MWCNTs‐Pd nanocatalyst was synthesized through covalent grafting of baclofen molecules onto surface‐modified carbon nanotubes and immobilizing Pd nanoparticles by the baclofen ligands. The chemical structure of the produced nanocatalyst was studied by Raman spectroscopy, Fourier transform‐infrared spectroscopy, energy‐dispersive spectroscopy (EDS), elemental mapping and inductively coupled plasma analysis. Also, its surface morphology was determined using the scanning and transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…These results indicated the successful bonding of 5‐aminomphthalic acid methyl ester to the surface of DAS through esterification. In the spectra of DAS2‐AT, the CO (amide I) and N − H (amide II) bending bonds were observed at 1656 and 1522 cm −1 , 36 respectively. This implied that –NH 2 group was grafted onto the surface of the functionalized DAS‐NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated the successful bonding of 5‐aminomphthalic acid methyl ester to the surface of DAS through esterification. In the spectra of DAS2‐AT, the CO (amide I) and N − H (amide II) bending bonds were observed at 1656 and 1522 cm −1 , 36 respectively. This implied that –NH 2 group was grafted onto the surface of the functionalized DAS‐NH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Later, a baclofen‐MWCNTs‐Pd nano‐ catalyst was introduced by Hekmati for the Sonogashira coupling. [ 100 ] The catalyst was prepared through covalent grafting of baclofen molecules onto surface‐modified multi‐walled carbon nanotubes and immobilizing PdNPs by the baclofen ligands. Aryl iodides and bromides were coupled with phenylacetylene with 0.2 mol% of the catalyst loading to give excellent yields.…”
Section: Classical Sonogashira Coupling Reactionsmentioning
confidence: 99%
“…In addition, the supported catalyst prepared by pramipexole had no potential for large‐scale industrial application. Similarly, the same research group also recently reported the functionalization of MWCNTs by the drug baclofen to support Pd NPs and catalyze Sonogashira reactions …”
Section: Carbon Nanotubesmentioning
confidence: 99%